Epstein–Barr virus infection induces genome‐wide de novo DNA methylation in non‐neoplastic gastric epithelial cells. Issue 4 (25th May 2017) - Matsusaka, Keisuke; Funata, Sayaka; Fukuyo, Masaki; Seto, Yasuyuki; Aburatani, Hiroyuki; Fukayama, Masashi; Kaneda, Atsushi
Abstract: Epstein–Barr virus (EBV)‐positive gastric cancer (GC) shows a higher DNA methylation epigenotype. EBV infection can causally induce genome‐wide aberrant DNA methylation, as previously demonstrated by in vitro infection experiments in the low‐methylation GC cell line MKN7. However, whether EBV exerts DNA methylation remodelling properties in non‐neoplastic epithelial cells remains unclear. Here we performed post‐infection time‐series DNA methylation analyses using the immortalized normal gastric epithelial cell line GES1. Genome‐wide analysis using Illumina's Infinium 450 k BeadArray demonstrated global de novo DNA methylation from post‐infection day 17, which was completed by 28 days in a manner similar to that observed in MKN7 cells. De novo methylation of all types of GC‐specific methylation marker genes was observed, indicating that EBV infection is sufficient for gastric epithelial cells to acquire an EBV‐positive GC epigenotype. Pyrosequencing demonstrated that methylation of the viral genome preceded that of the host cellular genome, suggesting the existence of well‐ordered mechanisms that induce methylation. Spatiotemporal representation with differential models revealed dynamic alterations of DNA methylation in promoter regions, occurring from lower‐CpG peripheral regions and extending to higher‐CpG core regions. In summary, EBV infection exerted powerful pressure to induce global de novo DNA methylation in non‐neoplastic cells within a month in a spatiotemporally well‐ordered manner. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.